(3GdYOI ddcQH hGdTOIs - (3VjGA GdOjf GdebOSj , eMeO Hf YHO GdhGMO Hf CMeO Hf YHO GdQMef GdSYOj GdebOSj, VjGA GdOjf CHh YHO Gddg,J (B643 (3g` s
(3ChdgG (B:s
(3CNHQJfG GdeQCJGf GdLdjdJGf Ce eMeO SJ GdfYe hHfJ NGdgG Ce eMeO SJ GdhRQGA Ef GdfHi Udi Gddg Ydgj hSde cGf jOYh YfO GdcQH dG Edg ZdG Gddg GdYXje GdMOjK s
(3BNQgG (B:s
(3Gddge Efi CSGdc aQLkG YGLdkG hQRbG hGSYkG s
(3SeGY BNQ Ydi GdTjN CHj GdMSf Ydi Hf eMeO gGQhf GdKYdHi Yf eUfaI HbQGAI Ydi Hf YHO GdcGai GdSHci SfI (B708 (3HNW Hf Yeg YHO GddWja Hf jMji GdSHci QhGjI Ce eMeO GdMGQKjI hCe eMeO GdKYdHjI s
(3jdjg LRA ef cJGH GdOhQ GdCZdi HTQM GdOhQ GdCYs
(3HgG fXGe GdJYbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B263s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs